1985
DOI: 10.1152/jappl.1985.58.5.1511
|View full text |Cite
|
Sign up to set email alerts
|

Role of ascorbic acid in chicks exposed to high environmental temperature

Abstract: This study was conducted to determine if ascorbic acid (AA) 1) increases resistance to high environmental temperature in young chickens and 2) alters heat-induced changes in several physiological responses. Groups of male chicks received either a standard ration containing 1,000 mg/kg (ppm) of AA or the ration without AA. Chicks were brooded for 3 wk and then maintained at 22 +/- 0.8 degrees C. At 4 wk of age, both AA-supplemented and control chicks were exposed to 30 min of heating (43 +/- 0.1 degrees C and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
2
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 0 publications
5
37
2
1
Order By: Relevance
“…Spleen is the most important lymphoid organ and combines the innate and adaptive immune response in a uniquely organized way. Pardue et al (1985) and Awadalla (1998) reported lighter spleen weight after chick's exposure to environmental stressors. The results of the present study showed that spleen of CL chicks was significantly heavier than that of SD chicks.…”
Section: Resultsmentioning
confidence: 99%
“…Spleen is the most important lymphoid organ and combines the innate and adaptive immune response in a uniquely organized way. Pardue et al (1985) and Awadalla (1998) reported lighter spleen weight after chick's exposure to environmental stressors. The results of the present study showed that spleen of CL chicks was significantly heavier than that of SD chicks.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the difference in the relative size of the bursa, the histologic study suggests that the changes were very limited, consisting of only a mild lymphoid depletion. This apparently contradictory result might be explainedby the protective effect of AA on immunological tissues and cell membranes from the insult of steroids (Pardue et al, 1985b). If this is the case, then the concentration of 500 ppm AA would seem to be adequate for this protection.…”
Section: Bursa Of Fabriciusmentioning
confidence: 99%
“…Kafri and Cherry (1984) also reported a greater body weight in 36-day-old heat-stressed broilers fed a diet supplemented with 100 ppm AA. The immunosuppression mediated by heat stress in chickens has been found to be partially ameliorated by AA supplementation (Pardue et al, 1985b). The improvement, as assayed by the increased agglutinin levels to sheep red blood cells, was attributed to the decrease of endogenous adrenocortical hormones (Pardue et al, 1985b) as a result of the inhibition of C-21 and 11-0-hydrowlase in the steroidogenic pathway (Cooper and Rosental, 1962;Kitabchi, 1967).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, efficacy of this practice has not been scientifically proved in Nigeria. Dietary supplementation with vitamin C has been reported to be efficient in reducing effects of heat stress in chickens (Pardue et al, 1985;Pardue and Thaxton, 1986;Sahin, 2003;Mahmoud et al, 2004). Combining chilled water with vitamin C may be more useful.…”
Section: Introductionmentioning
confidence: 99%